The Fallacies of Lord Keynes General Theory. - Rueff, Jacques (Quarterly Journal of Economics, 1947)
The impact of Keynes' theory, 343. — I. Summary of the Keynesian theory, 344. — Criticism, 346. — II. The effects of the demand for cash balances: a metalUc regime, 347; foreign trade, 350; an inconvertible money regime, 351. — III. The origins of the Keynesian error, 354. — The lessons of experience, 357. — IV. An imperfect philosophy of unspecified rigidity, 358. — V. The political consequences of the General Theory, 362. — War-time experience, 366. — The outlook, 366.